2018
DOI: 10.5897/jmpr2018.6699
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cytotoxic and antitumor activity of perillaldehyde 1,2-epoxide

Abstract: The study aimed to evaluate cytotoxicity and antitumor activity of perillaldehyde 1,2-epoxide (PE), a pmenthane monoterpene derivative against four human tumor cell lines ovarian cancer (OVCAR-8), colon carcinoma (HCT-116), glioblastoma (SF-295) and leukemia (HL-60) using the colorimetric MTT assay. PE showed a high degree of inhibition of cell proliferation (GI = 95.66 to 99.71%) and IC 50 16.14 μM (± 1.86), 23.61 μM (± 1.13), 21.99 μM (± 2.64) and, 9.70 μM (± 1.01) against tumor cells, respectively. Then, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Histopathological analyses of the spleen, liver and kidney showed no morphological changes in mice dosed with PE. Hence, the authors concluded the PE (28) exhibits cytotoxic and anticancer properties via necrosis and apoptosis [55]. Andrade and co-workers [24] prepared several compounds occurring in essential oils of various groups of plants.…”
Section: Perillaldehyde and Its Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Histopathological analyses of the spleen, liver and kidney showed no morphological changes in mice dosed with PE. Hence, the authors concluded the PE (28) exhibits cytotoxic and anticancer properties via necrosis and apoptosis [55]. Andrade and co-workers [24] prepared several compounds occurring in essential oils of various groups of plants.…”
Section: Perillaldehyde and Its Derivativesmentioning
confidence: 99%
“…Histopathological analyses of the spleen, liver and kidney showed no morphological changes in mice dosed with PE. Hence, the authors concluded the PE (28) exhibits cytotoxic and anticancer properties via necrosis and apoptosis [55]. A novel agent, perillaldehyde 1,2-epoxide (PE) 28 (Figure 15) was studied to estimate its cytotoxicity and antitumor activity against a few human tumor cell lines.…”
Section: Perillaldehyde and Its Derivativesmentioning
confidence: 99%